2019
DOI: 10.1001/jamanetworkopen.2019.13123
|View full text |Cite
|
Sign up to set email alerts
|

Association of Neurocognitive and Physical Function With Gait Speed in Midlife

Abstract: IMPORTANCE Gait speed is a well-known indicator of risk of functional decline and mortality in older adults, but little is known about the factors associated with gait speed earlier in life. OBJECTIVES To test the hypothesis that slow gait speed reflects accelerated biological aging at midlife, as well as poor neurocognitive functioning in childhood and cognitive decline from childhood to midlife. DESIGN, SETTING, AND PARTICIPANTS This cohort study uses data from the Dunedin Multidisciplinary Health and Develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 37 publications
3
104
0
Order By: Relevance
“…Similarly, the proportion of incorrect or incomplete texts increased with age and rose exponentially in the 50-59 and 60-plus age groups. One explanation for our findings is that texting-while-walking may be a sensitive test of age-associated neurodegenerative disease, since it has been found that some domains of cognitive function (such as reasoning and verbal fluency) show evidence of decline from middle age (45-49 years) [6,18].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Similarly, the proportion of incorrect or incomplete texts increased with age and rose exponentially in the 50-59 and 60-plus age groups. One explanation for our findings is that texting-while-walking may be a sensitive test of age-associated neurodegenerative disease, since it has been found that some domains of cognitive function (such as reasoning and verbal fluency) show evidence of decline from middle age (45-49 years) [6,18].…”
Section: Discussionmentioning
confidence: 87%
“…Structural and functional brain imaging studies have shown that cognition and motor control share common brain pathways, particularly in the prefrontal and temporal areas [4]. These areas play a crucial role in executive functioning, and seem to be particularly vulnerable to change with "normal ageing" [5,6]. Some age-related changes in gait performance are compensatory and beneficial to maintain stability and reduce the risk of falls, while other changes result in increased risk of injury [5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, one previous study has shown that hand grip strength was significantly associated with gait stability [13]. Recently, two longitudinal studies examined the association between gait velocity and physical performance [27,28]. Results from those studies indicate that gait speed and physical performance independently predict the risk of all-cause mortality [27]; therefore, both gait velocity and physical fitness serve as significant factors to determine the level of successful aging.…”
Section: Discussionmentioning
confidence: 99%
“…Results from those studies indicate that gait speed and physical performance independently predict the risk of all-cause mortality [27]; therefore, both gait velocity and physical fitness serve as significant factors to determine the level of successful aging. Another longitudinal study has shown that slow gait was associated with poor physical function, concluding that gait velocity should be a summary index of lifelong aging and could be a potential screening tool for physical and functional decline [28].…”
Section: Discussionmentioning
confidence: 99%
“…Gait speed was assessed under 3 walking conditions: usual gait speed (walk at normal pace from a standing start, measured as a mean of 2 walks) and 2 challenge paradigms, dual-task gait speed (walk at normal pace while reciting alternate letters of the alphabet out loud, starting with the letter "A," measured as a mean of 2 walks) and maximum gait speed (walk as fast as safely possible, measured as a mean of 3 walks). We calculated the mean of the 3 individual walk conditions to generate our primary measure of composite gait speed (Rasmussen et al, 2019).…”
Section: Supplemental Materialsmentioning
confidence: 99%